Family Psychoeducation (FPE) Meningkatkan Harga Diri dan Menurunkan Stigma Negatif Keluarga dalam Merawat Orang dengan Gangguan Jiwa - Sumirta, I Nengah; Candra, I Wayan; Ari Kresna Dewi, Ni Luh Gede; Harini, I Gusti Ayu (Jurnal Gema Keperawatan, 2025)
Mental health is health related to a person's emotional, mental and psychological condition. The root of mental health problems is very complex and diverse, involving biological, psychological, social and genetic factors. Events in life that have a major impact on a person's personality and behavior can affect their mental health. The purpose of this study was to determine the effect of Family Psychoeducation on stigma and family self-esteem in caring for family members with mental disorders at home. This type of research is a quantitative pre-experimental study, with a one group pre-post test design. Sampling using purposive sampling technique, sample size 45 people. Data were collected using the Rosenberg Self Esteem Scale (RSES) questionnaire to measure the level of self-esteem and Family stigma is measured by the Community Attitude Toward The Mentally (CAMI) scale. The variables studied were family stigma and self-esteem. The results of the pre-test showed an increase in negative stigma and a decrease in family self-esteem while providing home care with one of their family members with mental disorders. In the post-test, there was a decrease in negative stigma and an increase in self-esteem. The results of the Paired Sample Test on stigma and self-esteem obtained a p value = 0,000. There is an effect of Family Psychoeducation on reducing negative stigma and increasing self-esteem. It is recommended that families improve their ability to care for patients and the research site is advised to carry out Family Psychoeducation interventions routinely to family members who accompany family members with mental disorder who are undergoing outpatient treatment at the mental health clinic.